2003
DOI: 10.1034/j.1600-0706.2003.12134.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural plasticity in relation to egg and time limitation: the case of two fly species in the genus Anastrepha (Diptera: Tephritidae)

Abstract: Díaz -Fleischer, F. and Aluja, M. 2003. Behavioural plasticity in relation to egg and time limitation: the case of two fly species in the genus Anastrepha (Diptera: Tephritidae). -Oikos 100: 125-133.Reproductive opportunities in insects that deposit their eggs in discrete resource patches are frequently limited because the availability of oviposition substrates is often spatially and temporally restricted. Such environmental variability leads individuals to confront time-or egg-limitation constraints. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 40 publications
(50 reference statements)
3
48
0
Order By: Relevance
“…Multiple ectoparasite infestations have implications for total parasite intensity and thus, the level of impact sustained by the host. The propensity of parasitic insects to oviposit on a previously infested host is influenced by a number of factors, including the detection of host-marking pheromone from previous ovipositing females (Arredondo and Diaz-Fleischer 2006), host density and distribution (Cronin and Strong 1999;Diaz-Fleischer and Aluja 2003), female egg load (Minkenberg et al 1992), costs of larval competition (Dukas et al 2001), and competition between unrelated conspecifics (Frank 1994;Atkinson et al 2002;Puustinen et al 2004). Our findings support previous studies of Philornis that have documented or suggest multiple infestations (reviewed in O'Connor et al unpublished), though multiple infestations by P. downsi have not previously been confirmed in nests of Darwin's finches (Fessl et al 2006a).…”
Section: P Downsi Multiple Infestationsmentioning
confidence: 99%
“…Multiple ectoparasite infestations have implications for total parasite intensity and thus, the level of impact sustained by the host. The propensity of parasitic insects to oviposit on a previously infested host is influenced by a number of factors, including the detection of host-marking pheromone from previous ovipositing females (Arredondo and Diaz-Fleischer 2006), host density and distribution (Cronin and Strong 1999;Diaz-Fleischer and Aluja 2003), female egg load (Minkenberg et al 1992), costs of larval competition (Dukas et al 2001), and competition between unrelated conspecifics (Frank 1994;Atkinson et al 2002;Puustinen et al 2004). Our findings support previous studies of Philornis that have documented or suggest multiple infestations (reviewed in O'Connor et al unpublished), though multiple infestations by P. downsi have not previously been confirmed in nests of Darwin's finches (Fessl et al 2006a).…”
Section: P Downsi Multiple Infestationsmentioning
confidence: 99%
“…Thus, a polyphagous insect with high behavioral adaptability, as A. obliqua, may keep a large number of hosts. Several authors (Carey et al 1986;Prokopy & Reynolds 1998;Díaz-Fleischer & Aluja 2003a, 2003b) and the present study have reported the plasticity of fruit flies concerning their oviposition behavior strategies. In this sense, further investigations on the factors related to this behavior are needed.…”
Section: Discussionmentioning
confidence: 92%
“…Birke et al (2006) discuss the role of the longer aculeus in A. ludens that allows oviposition deeper into the peel and may be an adaptation for survival of eggs and early instars in citrus. Aluja et al (2001) and Dṍaz-Fleischer and Aluja (2003aAluja ( , 2003b review several differences in egg production and oviposition in A. ludens and A. obliqua. Fruit odors and odors from other reproducing females were noted to affect A. obliqua reproduction but not A. ludens.…”
Section: Records Of Hosts For West Indian Fruit Flymentioning
confidence: 97%